Attention Deficit Hyperactivity Disorder and Social Skills among Riyadh’s Primary School Students - Sultan Mousa Al-Owidha; Nevien Mohamed Zahran (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Students with mental deficits have worse academic and extracurricular performance. The little emphasis placed on the mental attitude of schoolchildren is a hindrance to their academic performance. This study aims to examine the correlation between Attention Deficit Hyperactivity Disorder (ADHD) and gender inequalities among Riyadh's elementary schoolchildren. This study's samples comprised 200 elementary-aged youngsters of both sexes, aged 9 to 13 years. For data analysis, the partial least square method is utilized. ADHD is shown to impact the social abilities of kids of both genders. It is advised that schools embrace such training and counseling programs to improve children's social skills. Such developmental initiatives must engage both parents and educators. This study has important theoretical, practical, and methodological implications for the field of literature. The next directions of this research are crucial for expanding our understanding of ADHD.